ІСТОРІЯ УКРАЇНИ ЯК ІНСТРУМЕНТ ЕТНОПОЛІТИКИ (Zaporizhzhia Historical Review, 2021)
The article considers the problems of the Ukrainian historical science and education as well as their historical influence on interethnic relations and tolerant attitude to various nations developed in the society.